Microstructural, mechanical and friction properties of nano-graphite and h-BN added TiC-based composites. Issue 18 (15th December 2020) - Nguyen, Van-Huy; Delbari, Seyed Ali; Sabahi Namini, Abbas; Babapoor, Aziz; Le, Quyet Van; Jang, Ho Won; Shokouhimehr, Mohammadreza; Shahedi Asl, Mehdi; Mohammadi, Mohsen
Abstract: In this study, a graphite and h-BN added TiC-based ceramic was produced by spark plasma sintering at 1900 °C. The sinterability of the graphite-doped sample could be improved, because undesirable TiO2 oxide layers were generally eliminated at the temperature of 1300 °C. However, the co-addition of graphite and h-BN additives simultaneously had a destructive impact on the relative density of TiC because of the entrapped produced gases in the sintered composite at the high sintering temperature. According to the results, the introduced h-BN was partially reacted with the TiC/TiO2 compounds, forming in-situ TiB2 and TiB phases. The sample doped with graphite presented the most significant strength (over 630 MPa) where the relative density, grain size, and dispersion of the secondary phases were found as the influential factors. Finally, the highest coefficient of friction ( 0.33) was achieved for the TiC-graphite specimen due to the distribution of the graphite with weak bonding within the TiC matrix.